THREE SPECIES OF SARGASSUM (PHAEOPHYCEAE) WITH COMPRESSED PRIMARY BRANCHES IN THE GULF OF THAILAND - Noiraksar, Thidarat; Ajisaka, Tetsuro; Ogawa, Hisao (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
Three species of Sargassum with compressed primary branches, S. binderi Sonder, S. oligocystum Montagne and S. swartzii (Turner) C.A. Agardh, have been described from the Gulf of Thailand. S. swartzii is the first record of this species from the coast of Thailand. A key for these three species and for each species descriptions have been completed. The clear distinction among these three species is clearly shown and discussed. S. binderi has slender lanceolate leaves, a dentate margin along the compressed stem of its vesicles, and clear spines along the whole margin of the flattened receptacles. S. oligocystum has broader lanceolate leaves with an acute to rounded apex, almost entire, spherical vesicles, and only few spines on the margin of the slightly compressed receptacles. S. swartzii has linear lanceolate leaves, pointed or crowned vesicles, and few spines neat the tip of its almost terete receptacles.